Toward an Understanding of Tax Amnesties - Gil, Patricia,Holz, Justin E.,List, John A.,Simon, Andrew,Zentner, Alejandro (National Bureau of Economic Research, 2023)
In modern economies, when debt and trust issues arise, a partial forgiveness policy is often the solution to induce payment and increase disclosure. For their part, governments around the globe continue to use tax amnesties as a strategy to allow debtors to make amends for past misdeeds in exchange for partial debt forgiveness. While ubiquitous, much remains unknown about the basic facts of how well amnesties work, for whom, and why. We present a simple theoretical construct that provides both economic clarity into tax amnesties as well as insights into the necessary behavioral parameters that one must estimate to understand the consequences of tax amnesties. We partner with the Dominican Republic Tax Authorities to design a natural field experiment that is linked to the theory to estimate key causal mechanisms. Empirical results from our field experiment, which covers 125,452 taxpayers who collectively owe 5.2 billion (5.5% of GDP) in known debt, highlight the import of deterrence laws, beliefs about future amnesties, and tax morale for debt payment and increased disclosure. Importantly, we find large short run effects: our most effective treatment (deterrence) increased payments of known debt by 25% and hidden debt by 48%. Further, we find no evidence of our intervention backfiring on subsequent tax payments
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Steuerstrafrecht; Straffreiheit; Feldforschung; Dominikanische Republik; Field Experiments; Taxation; Subsidies; and Revenue